Social and economic factors and black-white disparities in cardiovascular health: A decomposition analysis - Nicole D. Fields; Daesung Choi; Shivani A. Patel (Elsevier, 2023)
Background: Cardiovascular health (CVH) in Black adults, and particularly in Black women, has lagged behind White adults for decades and contributes to higher mortality rates for Black adults. We quantified the contribution of five social and economic factors to observed racial disparities in CVH by gender. Methods: We analyzed data from N = 8,019 adults aged ≥20 years free of cardiovascular disease assessed in the National Health and Nutrition Examination Survey, 2011-2018. Social and economic factors included self-reported education, income, employment, food security, and marital status. CVH was measured using eight behavioral and clinical indicators. We utilized Kitagawa-Blinder-Oaxaca decomposition to quantify gendered racial differences in CVH accounted for by these factors. Results: Black women (mean CVH = 79.3) had a lower age-adjusted CVH score compared to White women (mean CVH = 82.3) (mean difference [MD] = −3.01; 95% CI: -5.18, −0.84). Social and economic factors accounted for a 3.26-point disadvantage (95% CI: -4.12, −2.40) and a 0.25-point CVH score advantage due to factors not accounted for in the model. In women, income had the largest coefficient associated with CVH score (b = −1.48; 95% CI: -2.04, −0.92). Among men, social and economic factors accounted for a 2.27-point disadvantage (95% CI: -2.97, −1.56) with educational attainment being the largest coefficient associated with CVH score (b = −1.55; 95% CI: -2.03, −1.06). However, the disadvantage in men was offset by a 1.99 CVH score advantage that was not accounted for by factors in the model resulting in no racial difference in age-adjusted CVH score (MD = −0.28; 95% CI: -3.78, 3.22). Conclusions: Racial differences in social and economic factors may contribute a large portion to the observed disparity in CVH between U.S. Black and White women.